2017
DOI: 10.3345/kjp.2017.60.6.175
|View full text |Cite
|
Sign up to set email alerts
|

Individualized ibuprofen treatment using serial B-type natriuretic peptide measurement for symptomatic patent ductus arteriosus in very preterm infants

Abstract: PurposePlasma level of B-type natriuretic peptide (BNP), an emerging, sensitive, and specific biomarker of hemodynamically significant patent ductus arteriosus (PDA), rapidly decreases in infants receiving cyclooxygenase inhibitors for ductal closure. We investigated the usefulness of serial BNP measurement as a guide for individual identification of early constrictive responses to ibuprofen in preterm infants with symptomatic PDA (sPDA).MethodsBefore March 2010, the standard course of pharmacological treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Shin et al stopped treatment with ibuprofen in infants with a PDA when BNP concentration dropped to less than 600 pg/mL, resulting in fewer doses of ibuprofen in the group whose treatment was tailored based on BNP. (18)…”
Section: Diagnosismentioning
confidence: 99%
“…Shin et al stopped treatment with ibuprofen in infants with a PDA when BNP concentration dropped to less than 600 pg/mL, resulting in fewer doses of ibuprofen in the group whose treatment was tailored based on BNP. (18)…”
Section: Diagnosismentioning
confidence: 99%
“…However, no cutoff value of baseline BNP level was established to predict the efficacy of ibuprofen in premature neonates with hsPDA. Shin et al ( 80 ) found that ibuprofen can be stopped when the estimated BNP level is lower than 600 pg/mL to avoid unnecessary cyclooxygenase inhibitor doses and that this does not increase catheter closure failure and short-term morbidity related to sPDA. Moreover, King et al ( 81 ) used the BNP level to assess the use of acetaminophen in infants with hsPDA older than 2 weeks, and the BNP level of some infants with hsPDA decreased after treatment.…”
Section: Manuscript Formattingmentioning
confidence: 99%
“…(3) difficulty in maintaining the blood pressure, i.e., hypotension (the lower limit of normal mean arterial pressure was regarded to corrected gestational age) without response to loading fluid and infusion of dopamine; (4) a worsening ventilator status; and (5) chest radiographic evidence, i.e., pulmonary congestion or cardiomegaly (a cardiothoracic ratio >60%) with increased pulmonary flow. Symptomatic PDA was defined as the presence of two of these five signs with the confirmation of a large left to right ductal flow by color flow Doppler echocardiography (11).…”
Section: Clinical Datamentioning
confidence: 99%